Rancang Bangun Aplikasi Pembelajaran Doa Islami Dengan Pendekatan Multimedia Interaktif Menggunakan MDLC - Athaya Fawwaz, Raihan; Azrino Gustalika, Muhamad (JATISI, 2024)
SD Islam Terpadu Harapan Bunda is an elementary school established by Yayasan Permata Hati Purwokerto, focusing on academic knowledge along with Islamic religious values. Currently, the teaching and learning activities at SDIT Harapan Bunda primarily rely on conventional teaching methods, especially for lessons on Islamic prayers. Observations conducted at the school indicate the need for an interactive and innovative learning application to help and facilitate students in learning daily prayers, both within and outside the school environment. The aim of this research is to develop an educational application based on interactive and innovative multimedia for Android devices to assist in teaching Islamic prayers at SDIT Harapan Bunda Purwokerto. The Multimedia Development Life Cycle is used as the method in the application development process. The application functionality is tested using Black Box testing, and the System Usability Scale (SUS) method is employed to measure the application's usability. Black Box testing results show that the application functions optimally. Additionally, the SUS test results indicate a score of 80.7, categorized as acceptable, grade A-, and rated as good